International student mobility: Patterns and trends* - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
Over the past 10-15 years international student mobility has become an increasingly important part of the global higher education landscape. The total number of mobile tertiary education students was estimated to have reached more than 2.7 million in 20051 , a nearly 61 per cent increase since 19992. Significant changes in the infrastructures and capacity of higher education systems across the world partially explain why there has been such growth in such a short time.